ANXIETY IN STUDENTS’ PHONOLOGICAL AND GRAMMATICAL ARABIC LEARNING AT MTS NU 19 PROTOMULYO - Afgani, Rahardian Al; Inayah, Inayah; Abu Samra, Asma’ Naim Jamil; Aini, Tuti Qurrotul (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study examines the forms, causes, and impacts of student anxiety in learning Arabic phonology and grammar at MTs NU 19 Protomulyo. Employing a descriptive qualitative approach with limited quantitative support, the research utilizes classroom observations, semi-structured interviews, document analysis, and an adapted Foreign Language Classroom Anxiety Scale (FLCAS). Participants were purposively selected, focusing on students exhibiting linguistic anxiety, with the Arabic teacher serving as a key informant. Findings indicate that students experience communication apprehension, test anxiety, and fear of negative evaluation, particularly in pronunciation and grammatical usage (nahwu-ṣharaf). These anxieties stem from low self-confidence, assessment pressure, and classroom social dynamics, which together reduce participation and comprehension. The study underscores the need for effective supportive teaching strategies to improve Arabic language learning